Leptomeningeal Carcinomatosis From Carcinoma of Unknown Primary in a Young Patient: A Case Report and a Literature Review. (August 2019) - Moosavi, Leila; D'Assumpcao, Carlos; Bowen, Jonathan; Heidari, Arash; Cobos, Everardo
Leptomeningeal carcinomatosis, leptomeningeal meningitis, or, as referred here, leptomeningeal metastasis (LM), is a rare but frequently fatal complication seen in advanced stage of cancer either locally advanced or after a metastasis of a known primary cancer. We present a rare and uncommon case of leptomeningeal metastases from carcinoma of unknown primary. A 32-year-old female was diagnosed with LM; however, no known primary carcinoma was identified after 2 separate biopsies. The first biopsy of the right pre-tracheal lymph node showed poorly differentiated pan-keratin (AE1 and AE3) and placental alkaline phosphatase with the possibility of germ cell origin. Second cytology of cervical lymphadenopathy was remarkable for cytokeratin 7 and 20, placental alkaline phosphatase, and CDX2 suggestive of germ line tumor with both mucinous ovarian and gastrointestinal carcinomas. Unfortunately, the LM progressed rapidly despite multiple cycles of germ cell origin directed systemic and intrathecal chemotherapy, and the patient opted for hospice care without getting a chance to identify the primary source.